Why do people pay for news? The mediating effect of price tolerance - Ma, Xiaolin; Zhang, Chenglong (Frontiers in Communication, 2026)
IntroductionGenerative AI is transforming news production, and digital news platforms face challenges in sustaining user willingness to pay as they shift to subscription models. While perceived value affects subscription decisions, which aspects of value most influence price acceptance remains unclear. This study, therefore, examines whether functional, emotional, and social value are differentially associated with users’ willingness to pay for digital news, and whether price tolerance acts as a psychological mechanism linking value perceptions to payment intentions.MethodsAn online survey was conducted with 357 Chinese users who evaluated their experiences with digital news content. We proposed eight hypotheses based on consumption value theory and equity theory and tested them using confirmatory factor analysis and structural equation modeling.ResultsEmotional and social value are positively and significantly associated with price tolerance, whereas functional value is not. All three value dimensions are positively associated with willingness to pay, and price tolerance shows an indirect effect association between emotional and social value and willingness to pay. These findings identify distinct pathways through which experiential value is associated with subscription intentions.DiscussionTaken together, the results highlight that enhancing emotional resonance and fostering social identity may be more effective than improving functional utility alone in encouraging users to accept paywalls. The study offers theoretical insights into the value–tolerance–payment connection and provides practical guidance for designing sustainable digital news subscription strategies.